MEMBANGUN SDM KESEHATAN UNGGUL: MENJEMBATANI KESENJANGAN KUALITAS DAN KUANTITAS UNTUK MASA DEPAN SISTEM KESEHATAN INDONESIA - Aisyah Putri Amanda; Riswandy Wasir, Firda Syafitri Nurani (CV. Adiba Aisha Amira, 2024)
This study aims to The study aims to identify and evaluate the gaps in the quantity and quality of healthcare human resources in Indonesia, as well as to provide strategic recommendations for improvement. The main issues are the uneven distribution and imbalance of healthcare personnel, particularly in remote, border, and island regions. The research method used is a literature review with an in-depth analysis of journals and articles from online databases such as Google Scholar, Garuda, and PubMed within the period of 2020-2024. The study results indicate significant disparities between the education and practical skills of healthcare workers, limited access to medical technology, and a lack of opportunities for advanced education. Additionally, the uneven distribution of healthcare workers and insufficient incentives for those working in remote areas were found. To address these gaps, comprehensive strategies are needed, including improving the welfare of healthcare workers, enhancing healthcare infrastructure, raising education standards, and providing continuous training programs. With the implementation of these strategies, it is expected that the quality and quantity of healthcare human resources in Indonesia will improve, leading to more equitable and optimal healthcare services across all regions.